Multidimensional mechanisms and therapies underlying gastroesophageal reflux disease: focus on immunity, signaling pathways, and the microbiota-gut-brain axis - Zheng, Jiajing; Tao, Lin (Frontiers in Immunology, 2025)
Gastroesophageal reflux disease (GERD) has a high incidence rate and a complex pathogenesis that is not yet fully understood. This review aims to provide a comprehensive exploration of the mechanisms underlying GERD, emphasizing the interplay between immune responses, signaling pathways, and the microbiota-gut-brain axis. Specifically, it highlights the contributions of immune cells (e.g., T-lymphocytes, dendritic cells, mast cells), pro-inflammatory cytokines, and key signaling pathways, including nuclear factor (NF)-κB, mitogen-activated protein kinase (MAPK), and phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt), in driving esophageal inflammation and barrier dysfunction. Furthermore, the review examines the bidirectional interactions between psychological stress, gut microbiota dysbiosis, and GERD pathophysiology via the gut-brain axis. In bridging these mechanisms to potential therapeutic strategies, this review evaluates both established pharmacological treatments, such as proton pump inhibitors (PPIs) and immunotherapy, and emerging approaches, including herbal formulations and neuromodulation techniques. By synthesizing current evidence, the review identifies critical knowledge gaps, particularly in understanding the cross-talk between immune pathways and therapeutic targets. These findings underscore the need for mechanism-driven research to facilitate the development of personalized treatment strategies and address unresolved challenges in GERD management.